Hubungan antara Lokasi Endometriosis dengan Jumlah Kehamilan di Klinik Obgyn RSHS - Shinta Priwardani; Hidayat Widjajanegara; Julia Hartati (Jurnal Riset Kedokteran, 2024)
Abstract. Endometriosis is the growth of endometrial tissue outside the uterine cavity or located in the uterine cavity. Infertility is a serious problem for married couples, endometriosis is the gynecological disease that most often causes infertility in patients, with an incidence rate 10% of women in the world. Blockage of the fallopian tubes due to adhesions is one of the main mechanisms for infertility in endometriosis patients. This study aims to analyze the relationship between the location of endometriosis and the number of pregnancies at the OBGYN clinic of Hasan Sadikin Hospital in 2022. This study is a cross-sectional study of 40 patients. Data were obtained from medical records in the form of age characteristics, pregnancy history and number of pregnancies. Data were analyzed using the Anova statistical test. Results: this study obtained the characteristics of endometriosis patients, the majority were >40 years old 40%, had never had 1 and 2 pregnancies 37.5% and had endometriosis in the ovary location as many as 30 people 75% and the uterus as many as 8 people 20%. The Chi-Square test obtained a p-value of 0.636, where the value is greater than 0.05, so there is no significant relationship between the location of endometriosis and infertility in OBGYN clinic patients at Hasan Sadikin Hospital in 2022. Abstrak. Endometriosis adalah pertumbuhan jaringan endometrium yang berada di luar rongga rahim atau kavum uteri. Infertilitas merupakan masalah yang serius bagi pasangan suami istri, endometriosis merupakan kelainan ginekologi yang paling sering menyebabkan infertil pada pasien, dengan angka kejadian 10% pada wanita di dunia. Tersumbatnya tuba Fallopii karena adhesi menjadi salah satu mekanisme utama terjadinya infertilitas pada pasien endometriosis. Penelitian ini bertujuan untuk menganalisis hubungan antara lokasi endometriosis dengan jumlah kehamilan di klinik OBGYN RS Hasan Sadikin tahun 2022. Penelitian ini merupakan penelitian cross sectional pada 40 pasien. Data diperoleh dari rekam medis berupa karakteristik usia, riwayat kehamilan dan jumlah kehamilan. Data dianalisis dengan uji statistik Anova. Hasil: penelitian ini didapatkan karakteristik pasien endometriosis, mayoritas berusia >40 tahun 40%, tidak pernah mengalami kehamilan sebanyak 1 dan 2 kali 37.5% dan mengalami endometriosis di lokasi ovary sebanyak 30 orang 75% dan uterus sebanyak 8 orang 20%. Uji Chi-Square diperoleh p-value sebesar 0.636 dimana nilai tersebut lebih besar dari 0.05, maka tidak terdapat hubungan yang signifikan antara Lokasi endometriosis dengan infertilitas pada pasien klinik OBGYN RS Hasan Sadikin tahun 2022.